CSR MAPPING: Swiss stakeholder salience, concerns, and ethics - Looser, S.; Wehrmeyer, Walter (-, 2014)
Previous research on Corporate Social Responsibility (CSR) in Switzerland has made few attempts to identify actual and potential stakeholders and their diverging contributions to this topic. Using stakeholder map methodology, showing power, urgency, legitimacy, and concerns of different actors, the paper investigates the current state of Swiss CSR. To derive this map, publicly available documents were explored, augmented by 27 interviews with key stakeholders (consumers, media, government, trade unions, Non-Profit Organisations (NPOs), banks, certifiers, and consultants) and management of different companies (Multinational Enterprises (MNEs), Small- and Medium-sized Enterprises (SMEs), and large national companies). Using MAXQDA, the quantified codes given for power, legitimacy, and urgency were transferred into stakeholder priorities or, in other words, into positions in the map. Further, the codes given in the interviews for different CSR interests and the results from the document analysis were linked between stakeholders. The identified concerns and priorities were quantitatively analysed in regard to centrality and salience using VennMaker.The paper found SMEs, MNEs, and cooperating NPOs as being the most significant stakeholders. Swiss CSR is therefore not primarily driven by regulators, market pressure, or customers. Further network parameters substantiated the importance of SMEs while following an unconventionally informal, but innovative, vibrant, and practical CSR approach, emerging for reasons alter than conventional agendas are supposed to evolve. In fact, the findings may point at a very different and highly sophisticated role businesses have adopted in Switzerland, manifesting in democratic decisions and abolished hierarchies, handshakes instead of formal contracts, and transparency in all respects (e.g. performance indicators, salaries, and bonuses). Hence, as a new stance and argument within CSR related research, this paper concludes that “informal” does not mean “weak”.